Exploration of the diversity of local green fodder of goats in North Biak District, Biak Numfor Regency - Tethool, Rina M.E.S; Santoso, Budi; saragih, Evi Warintan (Fakultas Peternakan Universitas Papua, 2025)
Sustainable goat production in North Biak District, Papua, depends heavily on locally available forages, yet empirical information on species diversity remains limited. This study described the forage plants fed to goats by smallholders in four villages (Dofyo Wafor, Warsansan, Andey, Saukobye). Using a descriptive design, we conducted interviews and direct field observations with 20 purposively selected farmers. Forage taxa were identified to species level using field guides and plant-identification software; uncertain specimens were referred to the University of Papua’s Center for Biodiversity Research. We documented 12 forage species supplied to goats. The assemblage was dominated by woody plants—primarily trees and shrubs—with a small contribution from grasses. Ficus spp. were prominent within rations (e.g., F. maclellandii, F. racemosa, F. hispida, F. variegata), alongside other browse species such as Bauhinia glabra, Glochidion glomeratum, Macaranga hispida, Boehmeria nivea, Clerodendrum paniculatum, Garcinia dulcis, Morinda citrifolia, and Saccharum edule. By growth form, forages comprised approximately 67.7% trees, 25.0% shrubs, and 8.3% grasses. Several species reported dual use as ethnoveterinary resources (e.g., Glochidion glomeratum, Morinda citrifolia, Garcinia dulcis), indicating potential functional-feed roles beyond nutrition. Findings highlight a diverse, browse-dominated forage base that can be leveraged to support maintenance and production in smallholder goat systems. We recommend follow-up work on seasonal availability, nutritive value, and secondary-metabolite profiles to guide cultivation, ration formulation, and dry-season feeding strategies.